Actinobacillus pleuropneumoniaeculture supernatant antiviral effect against porcine reproductive and respiratory syndrome virus occurs prior to the viral genome replication and transcription through actin depolymerization. Issue 2 (February 2018) - Hernandez Reyes, Yenney; Provost, Chantale; Traesel, Carolina Kist; Jacques, Mario; Gagnon, Carl A.
Abstract : Purpose. : Recently, the strong antiviral activity of an Actinobacillus pleuropneumoniae ( App ) culture supernatant against porcine reproductive and respiratory syndrome virus (PRRSV) was discovered. Following this finding, the objective of the present study was to understand how the App culture supernatant inhibits PRRSV replication in its natural targeted host cells, i.e. porcine alveolar macrophages (PAMs). Methodology. : Several assays were conducted with App culture supernatant‐treated PRRSV‐infected cell lines, such as PAM, St‐Jude porcine lung and MARC‐145 cells. RT‐qPCR assays were used to determine the expression levels of type I and II IFN mRNAs, viral genomic (gRNA) and sub‐genomic RNAs (sgRNAs). Proteomic, Western blot and immunofluorescence assays were conducted to determine the involvement of actin filaments in the App culture supernatant antiviral effect. Results/Key findings. : Type I and II IFN mRNA expressions were not upregulated by the App culture supernatant. Time courses of gRNA and sgRNA expression levels demonstrated that the App culture supernatant inhibits PRRSV infection before the first viral transcription cycle. Western blot experiments confirmed an increase in the expression of cofilin (actin cytoskeleton dynamics regulator) and immunofluorescence also demonstrated a significant decrease of actin filaments in App culture supernatant‐treated PRRSV‐infected PAM cells. App culture supernatant antiviral activity was also demonstrated against other PRRSV strains of genotypes I and II. Conclusion. : App culture supernatant antiviral effect against PRRSV takes place early during PRRSV infection. Results suggest that App culture supernatant antiviral effect may take place via the activation of cofilin, which induces actin depolymerization and subsequently, probably affects PRRSV endocytosis. Other experiments are needed to fully validate this latest hypothesis.